Epithelial-mesenchymal transition as a therapeutic target for overcoming chemoresistance in pancreatic cancer - Elaskalani, O.; Razak, N.; Falasca, Marco; Metharom, Pat (BAISHIDENG PUBLISHING GROUP INC, 2017)
Pancreatic cancer has one of the worst prognoses among all cancers due to the late manifestation of identifiable symptoms and high resistance to chemo- and radiation therapies. In recent years, a cancer development phase termed epithelial-mesenchymal transition (EMT) has gained increasing research focus. The process is implicated in tumour metastasis, and emerging evidence suggests EMT also contributes or induces chemoresistance in several cancers. Nevertheless, the applicability of therapeutic targeting of EMT faces many challenges. In this mini-review, we summarise the evidence supporting the role of EMT in pancreatic cancer progression, focusing particularly on its association with chemoresistance.